Світлоглиняні амфори з рифленням типу набігаючої хвилі (IV—VII ст. н. е.) - Сазанов, А.В. (Археологія, 1992)
У статті розглядається один з найважливіших класів ранньовізантійської керамічної тари. В статье, посвященной одному из классов ранневизантийской керамической тары, предлагается его классификация по девяти типам. Анализ распределения амфор позволил сделать вывод, что их производство продолжалось от последней трети IV в. н. э. до третьей четверти VI в. н. э., в первой половине VII в. н. э. они выходят из употребления. Характер цикла показывает, что бытование этих амфор продолжалось до конца VII в., но в то время они уже не датируют комплексы. The paper is devoted to ope of the classes of early Byzantine pottery. It suggests Its classification by nine types. The analysis of the amphoras distribution has allowed a conclusion that their production had continued from the last third of the 4th century AC to the thitd fourth of the 6th century AC, in the first half of the 7th century AC they went out of use. A character of the cycle has shown that every day usage of these amphoras continued to the and of the 7th century but at the same they no lonher date the complexes.